Life - Lewis, Ricki; Goodenough, Judith; Moore, Randy (Dubuque, IA : Wm. C. Brown Publishers, 1995)
This text provides an introduction to biology. It features: expanded coverage of evolution; new chapters on biomes and the origins and diversity of life; a unit on behaviour and ecology; essays on bioethnic connections; and a discussion of chemistry.
Includes bibliographical references and index.
rpm 23/08/16
Loans
Keywords: Biology; Human biology